Медіація як альтернативний метод вирішення конфліктів у кримінальних справах: світовий огляд - Шардакова, Анастасія; Сорока, Світлана; Shardakova, Anastasiia; Soroka, Svitlana (Видавництво Львівської політехніки, 2024)
У статті розглянуто медіацію як одну із форм відновного правосуддя. Медіація – сучасний спосіб реагування на протиправну поведінку особи без звернення до суду. Такий підхід сприяє балансу інтересів суспільства, потерпілого, правопорушника. Відзначено, що медіація у кримінальному провадженні має позитивний аспект, пов’язаний зі зниженням судового навантаження, зменшенням витрат на утримання засуджених, а головною метою застосування медіації під час кримінального провадження є діалог між потерпілим та підозрюваним / обвинуваченим, виправлення особи, яка вчинила кримінальне правопорушення, пробудження відчуття відповідальності у правопорушника та надання йому можливості виправити ситуацію, відшкодувати завдану шкоду з можливістю подальшої ресоціалізації та реабілітації. Констатовано, що в Україні медіація стає дедалі популярнішою та актуальнішою альтернативою судовим процесам у вирішенні різних видів конфліктів. Акцентовано, що відсутність належного розуміння ефективності та потенціалу медіації серед правозастосовних органів, юридичних фахівців та громадськості може бути серйозною перепоною для упровадження цього методу вирішення конфліктів у кримінальних справах. Крім того приділено увагу досвіду зарубіжних країн і проаналізовано приклади успішного впровадження медіаційних процедур у кримінальних справах Норвегії, Італії, США, Швеції. Аналіз підтверджує, що міжнародні стандарти медіації – важливий інструмент вирішення правових спорів та конфліктів за межами судової системи. Зроблено висновок, що медіація як альтернативний метод вирішення конфліктів у кримінальних справах є дієвим та перспективним підходом, який дає змогу враховувати

The article discusses mediation as one of the forms of restorative justice. Mediation is a modern way of responding to unlawful behavior without resorting to court. This approach promotes a balance of interests between society, the victim, and the offender. It is noted that mediation in criminal proceedings has a positive aspect associated with reducing the judicial workload, reducing the costs of maintaining convicted individuals. The main goal of using mediation during criminal proceedings is to facilitate dialogue between the victim and the suspect / accused, rehabilitation of the offender, awakening a sense of responsibility in the offender, and providing them with an opportunity to rectify the situation and compensate for the harm caused, with the possibility of further reintegration and rehabilitation. It is stated that in Ukraine, mediation has become increasingly popular and relevant as an alternative to judicial processes in resolving various conflicts. It is emphasized that the lack of proper understanding of the effectiveness and potential of mediation among law enforcement agencies, legal professionals, and the public can be a significant obstacle to the implementation of this conflict resolution method in criminal cases. In addition, special attention is given to the experience of foreign countries, and examples of successful implementation of mediation procedures in criminal cases in Norway, Italy, the United States, and Sweden are analyzed. This indicates that international mediation standards serve as an important tool for resolving legal disputes and conflicts outside the judicial system. The conclusion is drawn that mediation as an alternative method of conflict resolution in criminal cases is an effective and promising approach that takes into account the interests of all parties involved, promotes the restoration of harmony in society, and reduces the burden on the judicial system. The widespread implementation of mediation in different countries confirms its success and importance in modern justice. However, to achieve full success, it is necessary to actively promote this method, ensure compliance of legislation with the requirements of mediation, increase public awareness, and enhance the professionalism of mediators. Mediation can play a crucial role in building a just society where conflicts are resolved through dialogue, understanding, and cooperation.
Mediation as an alternative method of conflict resolution in criminal cases: a global overview
Keywords: медіація; кримінальне правосуддя; міжнародні стандарти; світові тенденції; альтернативні методи вирішення конфліктів; mediation; criminal justice; international standards; global trends; alternative methods of conflict resolution; 343.137